Pengaruh Jahe dan Pir Kukus terhadap Kualitas Tidur Anak dengan ISPA Ringan - Nazwah Masiah; Budi Antoro; Anggie Stiexs (Universitas Nurul Jadid, 2026)
Acute Respiratory Infection (ARI) remains a major health problem among children and is associated not only with respiratory symptoms such as cough and rhinorrhea but also with impaired sleep quality due to nocturnal discomfort and breathing disturbances. Non pharmacological interventions, including the consumption of ginger and steamed pear (Japirkus), have been proposed as complementary therapies owing to their anti-inflammatory and natural expectorant properties. This study aimed to examine the effect of ginger and steamed pear consumption on sleep quality among children with mild ARI. This study employed a quantitative with quasi-experimental design with a pre-test and post-test with control group approach. The research sample consisted of 26 respondents (children aged 4-10 years) selected using a purposive sampling technique. Sleep quality was measured using the Children's Sleep Habits Questionnaire (CSHQ) instrument. The results showed that the mean sleep quality score in the intervention group decreased significantly from 71.46 (poor sleep quality) before the intervention to 48.69 after the intervention. Statistical analysis demonstrated a significant difference between the intervention and control groups (p = 0,008). These findings indicate that ginger and steamed pear consumption significantly improves sleep quality in children with mild ARI. Therefore, this non-pharmacological intervention may serve as an alternative approach for parents and healthcare education programs addressing environmental risk factors for ARI